Turning breaches from losses to wins. Issue 9 (September 2021) - Kadar, Tamas
Abstract : It seems that every year, a new record is set for the number of records exposed in data breaches. 1 In 2020, that number was 37 billion individual records, jumping a staggering 141% from 2019. Major breaches included the theft of information from approximately 5.2 million guests of the Marriott hotel chain and 2.3 million data points from a Brazilian biometrics company. 2, 3 Although the year is far from over, we can expect 2021 to be another record-breaking year, with the phone details of 533 million Facebook users already leaked. 4